INSPECT-PBEE: a performance-based earthquake engineering GUI for IDARC-2D - AlHamaydeh, Mohammad (2019)
Designs that are performance and functionality driven typically mandate the nonlinear analysis. Up To date, nonlinear analysis remains a sophisticated tool that may not appeal to majority of structural/earthquake practicing engineers due to the required effort, time and its iterative nature. There are several available commercial and research-oriented packages that perform nonlinear analyses. IDARC-2D is one of the powerful and freely available tools for nonlinear analyses. This paper presents INSPECT-PBEE which is a software pre/post processor package developed to facilitate the use of IDARC-2D program and automates the seismic performance evaluation of structures. It operates in two modes; a preprocessor and a post-processor, developed using C# programming language and .Net libraries. The preprocessor package simplifies the nonlinear modeling process on IDARC-2D using its useful Graphical User Interface (GUI). The post-processor component provides a powerful tool that automates the seismic performance assessment of structures using inelastic dynamic analyses. Furthermore, it has two options for evaluating the seismic performance, either user-specified criteria or following the well-established procedure described in the FEMA P695 document.